Prospects for China's economic development in the next decade - Shantong Li; Sanmang Wu; Jianwu He (China Finance and Economic Review, 2013)
This article discusses prospects for China's economic development over the next decade based on the computable general equilibrium (CGE) model of the Chinese economy. The article argues that the long-term trend of China's economy will remain positive and the major driving forces of the fast-growing Chinese economy still exist. However, particular focus must be placed on the changes in the domestic and international environment in the next decade. Further reforms should be promoted in the field of economic elements, public expenditure, energy, and the environment in order to improve the sustainability and balance of economic development.
Keywords: 330; China's economy; Review; Prospects